Community engagement to implement evidence-based practices in the HEALing communities study. (1st December 2020) - Sprague Martinez, Linda; Rapkin, Bruce D.; Young, April; Freisthler, Bridget; Glasgow, LaShawn; Hunt, Tim; Salsberry, Pamela J.; Oga, Emmanuel A.; Bennet-Fallin, Amanda; Plouck, Tracy J.; Drainoni, Mari-Lynn; Freeman, Patricia R.; et al.
Highlights: Community engagement can improve the uptake and sustainability of evidence-based practices (EBPs). The Healing Communities Study seeks to show how community engagement can support the adoption of EBPs for addressing the opioid crisis. To reduce opioid overdose deaths a community-engaged, data driven planning process is being implemented in 67 highly impacted communities. Abstract: Background: The implementation of evidence-based practices to reduce opioid overdose deaths within communities remains suboptimal. Community engagement can improve the uptake and sustainability of evidence-based practices. The HEALing Communities Study (HCS) aims to reduce opioid overdose deaths through the Communities That HEAL (CTH) intervention, a community-engaged, data-driven planning process that will be implemented in 67 communities across four states. Methods: An iterative process was used in the development of the community engagement component of the CTH. The resulting community engagement process uses phased planning steeped in the principles of community based participatory research. Phases include: 0) Preparation, 1) Getting Started, 2) Getting Organized, 3) Community Profiles and Data Dashboards, 4) Community Action Planning, 5) Implementation and Monitoring, and 6) Sustainability Planning. Discussion: The CTH protocol provides a common structure across the four states for the community-engaged intervention and allows for tailored approaches that meet the unique needs or sociocultural context of each community. Challenges inherent to community engagement work emerged early in the process are discussed. Conclusion: HCS will show how community engagement can support the implementation of evidence-based practices for addressing the opioid crisis in highly impacted communities. Findings from this study have the potential to provide communities across the country with an evidence-based approach to address their local opioid crisis; advance community engaged research; and contribute to the implementation, sustainability, and adoption of evidence-based practices. Trial registration: ClinicalTrials.gov (NCT04111939).